2020
DOI: 10.1111/hepr.13538
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a 13‐microRNA‐based signature and prognostic nomogram for predicting overall survival in patients with hepatocellular carcinoma

Abstract: Aim: Hepatocellular carcinoma (HCC) is a common malignancy associated with a poor prognosis due to difficulties in reliably estimating overall survival (OS). MicroRNAs (miRNAs) play critical roles in HCC initiation, progression, and metastasis and are highly correlated with patient prognosis. Thus, miRNA based risk signatures and nomograms are urgently required for predicting OS in patients with HCC. Methods: We constructed a 13 miRNA based signature and prognostic nomogram using 408 HCC samples and 58 normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…The model incorporating too many variables was not easy to use, which limited its clinical application. Besides, the robustness of predictive models was not given enough attention in the research of Zheng et al (41). An external validation in different population was needed to test the reliability of predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…The model incorporating too many variables was not easy to use, which limited its clinical application. Besides, the robustness of predictive models was not given enough attention in the research of Zheng et al (41). An external validation in different population was needed to test the reliability of predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…The risk score of each patient relied on the miRNA expression level and the regression coefficient obtained from the LASSO regression analysis. The risk score was calculated as follows: Risk score (miRNAbased classifier) = sum of coefficients × expression level of miRNAs, refer to previous description [34]. According to the median risk score value, 67 patients with HNSCC were divided into high-risk and low-risk groups.…”
Section: Construction Of Risk Score Formulamentioning
confidence: 99%
“…The C-index values were calculated to measure the predictive performance of the risk signature. All analyses were performed to compare the consistency between the primary and internal validated cohorts, refer to previous description [34].…”
Section: Assessment Of Mirna Signaturementioning
confidence: 99%
See 1 more Smart Citation
“…Each miRNA targets hundreds of mRNAs and downregulates them post-transcriptionally by base pairing with their 3′-untranslated regions (3′-UTRs) [ 10 , 11 ]. Extensive studies have revealed that miRNAs regulate various biological and cellular processes, including proliferation, differentiation, cell behavior, and cancer development [ 12 , 13 , 14 , 15 , 16 , 17 ]. The involvement of miRNAs in fibrosis of the liver and other organs also has been reported [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%